Sustained inhibition of progressive joint damage with rituximab plus methotrexate in early active rheumatoid arthritis: 2-year results from the randomised controlled trial IMAGE. Issue 3 (19th October 2011) - Tak, Paul P; Rigby, William; Rubbert-Roth, Andrea; Peterfy, Charles; van Vollenhoven, Ronald F; Stohl, William; Healy, Emma; Hessey, Eva; Reynard, Mark; Shaw, Tim
Abstract : Background: In the IMAGEstudy, rituximab plus methotrexate (MTX) inhibited joint damage and improved clinical outcomes at 1 year in MTX-naïve patients with early active rheumatoid arthritis. Objective: The aim of this study was to assess joint damage progression and clinical outcomes over 2 years. Methods: Patients (n=755) were randomised to receive rituximab 2×500 mg+MTX, 2×1000 mg+MTX or placebo+MTX. The placebo-controlled period continued to week 104. Two-year end points were defined as secondary or exploratory and included change in total Genant-modified Sharp score (mTSS), total erosion score and joint space narrowing score from baseline to week 104. Clinical efficacy and physical function end points were also assessed. Results: At 2 years, rituximab 2×1000 mg+MTX maintained inhibition of progressive joint damage versus MTX alone (mTSS change 0.41 vs 1.95; p<0.0001 (79% inhibition)), and a higher proportion of patients receiving rituximab 2×1000 mg+MTX had no radiographic progression over 2 years compared with those receiving MTX alone (57% vs 37%; p<0.0001). Contrary to 1-year results, exploratory analysis of rituximab 2×500 mg+MTX at 2 years showed that progressive joint damage was slowed by ∼61% versus placebo+MTX (mTSS, exploratory p=0.0041). Improvements in clinical signs and symptoms and physical function seen after 1 year in rituximab-treated patients versus those receiving placebo were maintained at year 2. Safety profiles were similar between groups. Conclusions: Treatment with rituximab 2×1000 mg+MTX was associated with sustained improvements in radiographic, clinical and functional outcomes over 2 years. Clinical trials.gov identifier NCT00299104 .